2002
DOI: 10.1029/2001jc001024
|View full text |Cite
|
Sign up to set email alerts
|

Evolution and dynamics of tropical river plumes in the Great Barrier Reef: An integrated remote sensing and in situ study

Abstract: [1] The short-lived but intense discharge of freshwater from tropical rivers into the Great Barrier Reef (GBR) Lagoon and the associated salinity reductions are a critical consideration in marine research and management of the ecologically sensitive GBR World Heritage Area. Salinity provides a unique tracer that gives clues to the origin of river-borne contaminants and allows the influences of storm-induced resuspension and river discharge on turbidity to be clearly distinguished. We describe a field investiga… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
9
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(9 citation statements)
references
References 32 publications
0
9
0
Order By: Relevance
“…Most environmental variables we examined on the Great Barrier Reef displayed strong cross‐shelf gradients such as salinity (Burrage et al. , 2002), temperature and chlorophyll (Liston et al.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Most environmental variables we examined on the Great Barrier Reef displayed strong cross‐shelf gradients such as salinity (Burrage et al. , 2002), temperature and chlorophyll (Liston et al.…”
Section: Discussionmentioning
confidence: 99%
“…Most environmental variables we examined on the Great Barrier Reef displayed strong cross-shelf gradients such as salinity (Burrage et al, 2002), temperature and chlorophyll (Liston et al, 1992) that are influenced by freshwater inputs and terrigenous influences near the coast, and by oligotrophic oceanic waters at the shelf edge. Indeed, the distance between the coast and the ocean increases from northern to southern sectors on the Great Barrier Reef; therefore, for northern sites both distances would be short, whereas for southern sites at least one of these distances would be long.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Although a limited number of studies reflect on potential implications of a complete lack of river outflows on marine environments, it is generally understood that changing the scale, frequency and seasonality of river outflows can have severe impacts on species that require food pulses for successful reproduction or larval survival (Drinkwater and Frank 1994;Whitfield and Marais 1999). Several studies have identified important relationships between outflow-stimulated productivity and populations of marine species and habitats as a result of these controls (Burrage et al 2002;De Robertis et al 2005;Burla et al 2010;Brookes et al 2015;Black et al 2016). There is also a critical period at the point of first feeding by larvae where the presence of suitable amounts and types of food determine year-class strength (Hjort 1914).…”
Section: Discussionmentioning
confidence: 99%